Analisis Faktor yang Mempengaruhi Pebisnis Menggunakan Media Sosial Instagram Sebagai Sarana Promosi - Shobah Sibtiyah; Muhammad Jamil Latief (Jurnal EMT KITA, 2023)
Online business competition (E-Commerce) in the business ecosystem has been massive because of its promising market potential. Instagram is a type of social media that is present in the community and seems to be used optimally as a marketing tool. But the debate about what factors stimulate business people to use it as a promotional medium is still being debated. So this study aims to determine what factors influence businessmen in using Instagram as a means of promotion. The study population came from businessmen who were confirmed to have business Instagram accounts in the East Jakarta area, non-probability sampling technique was used and obtained an observation sample of n = 33. Multiple linear regression analysis was used as an analytical knife with the independent variables Low Cost (X1), Feature Reliability (X2), and Target Consumers (X3), as well as the dependent variable of businessmen's decisions (Y). The results of the research H1 and H2 are accepted (X1 and X2 have an effect on Y), H3 is rejected (X3 has no effect on Y), H4 is accepted (X1, X2, and X3 simultaneously affect Y), and the R2 value is 60.2%. The research implication suggests that business people who use Instagram should pay attention to these factors in order to optimize promotions.